2012
DOI: 10.1590/s0034-71672012000500022
|View full text |Cite
|
Sign up to set email alerts
|

Ambiente virtual de aprendizagem no ensino de Enfermagem: relato de experiência

Abstract: New Technologies of Information / Communication offer the option of using a virtual learning environment (VLE), which allows for greater interactivity in daily nursing education urging educators to rethink their teaching practices. The aim of this study was to report the experience of the use of virtual environment in nursing education from the perspective of students. The discipline "Nursing Education: Trends and Challenges" was given to 78 students from the 4th semester of undergraduate nursing, from which 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
44

Year Published

2016
2016
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(61 citation statements)
references
References 2 publications
0
17
0
44
Order By: Relevance
“…It was found that the set of features designed for storage, distribution and management of course content, proceeded in a progressive, interactive and satisfactorily manner. 11 For studies and exams, students could use operating systems (Mac OS, Windows and Linux) with audio devices, speakers or headphones. As for browsers, free access was possible through Internet Explorer (version 9.0 or higher), Mozilla Firefox 3.0 (or higher), Safari and Google Chrome, emphasizing that variations between them showed no loss in visualize images, illustrations and animations, the last two could run on Windows Media Player and Adobe Flash Player.…”
Section: Stage 3 -Comparison: System Model Vs System Portraitmentioning
confidence: 99%
“…It was found that the set of features designed for storage, distribution and management of course content, proceeded in a progressive, interactive and satisfactorily manner. 11 For studies and exams, students could use operating systems (Mac OS, Windows and Linux) with audio devices, speakers or headphones. As for browsers, free access was possible through Internet Explorer (version 9.0 or higher), Mozilla Firefox 3.0 (or higher), Safari and Google Chrome, emphasizing that variations between them showed no loss in visualize images, illustrations and animations, the last two could run on Windows Media Player and Adobe Flash Player.…”
Section: Stage 3 -Comparison: System Model Vs System Portraitmentioning
confidence: 99%
“…Na literatura, temos encontrado trabalhos sobre o uso de AVA, principalmente, no ensino da enfermagem (CAMACHO, 2009;COGO et al, 2011;PRADO et al, 2012;PEDRO;SILVA et al, 2010) e da medicina na qual a produção está relacionada ao uso de simuladores em ambientes virtuais ou sobre o uso de AVA como reforço ao ensino presencial de disciplinas do ciclo básico, conforme apresentado por Mezzari et al (2012). No ensino de Ciências há pesquisas sobre diferentes contextos, tais como: ensino fundamental, na disciplina de Ciências (ZIEGLER et al, 2014) (2002) destacam como característica relevante de um AVA o potencial para apoiar a interação social.…”
Section: Fundamentação Teóricaunclassified
“…It can contribute to the widespread use of ICt in education because of the flexibility and low cost of deployment and use. this virtual learning environment enables the availability of themes and materials to support the development in the classroom and to carry out the activities of virtual classes [1].…”
Section: Showing Context Demonstrating That Current Technology Allowmentioning
confidence: 99%
“…In one of the first reports, it was argued that electronic networks exerted little influence on scientific communication because few teachers were users of networks. However, after a few years, the intensive use of the Internet has been reported as a strong influence in the scientific community, especially the e-mail and the web [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation